Precise Genome Editing in miRNA Target Site via Gene Targeting and Subsequent Single-Strand-Annealing-Mediated Excision of the Marker Gene in Plants - Ohtsuki, Namie; Kizawa, Keiko; Mori, Akiko; Nishizawa-Yokoi, Ayako; Komatsuda, Takao; Yoshida, Hitoshi; Hayakawa, Katsuyuki; Toki, Seiichi; Saika, Hiroaki (Frontiers in Genome Editing, 2021)
Gene targeting (GT) enables precise genome modification—e.g., the introduction of base substitutions—using donor DNA as a template. Combined with clean excision of the selection marker used to select GT cells, GT is expected to become a standard, generally applicable, base editing system. Previously, we demonstrated marker excision via a piggyBac transposon from GT-modified loci in rice. However, piggyBac-mediated marker excision has the limitation that it recognizes only the sequence TTAA. Recently, we proposed a novel and universal precise genome editing system consisting of GT with subsequent single-strand annealing (SSA)-mediated marker excision, which has, in principle, no limitation of target sequences. In this study, we introduced base substitutions into the microRNA miR172 target site of the OsCly1 gene—an ortholog of the barley Cleistogamy1 gene involved in cleistogamous flowering. To ensure efficient SSA, the GT vector harbors 1.2-kb overlapped sequences at both ends of a selection marker. The frequency of positive–negative selection-mediated GT using the vector with overlapped sequences was comparable with that achieved using vectors for piggyBac-mediated marker excision without overlapped sequences, with the frequency of SSA-mediated marker excision calculated as approximately 40% in the T0 generation. This frequency is thought to be adequate to produce marker-free cells, although it is lower than that achieved with piggyBac-mediated marker excision, which approaches 100%. To date, introduction of precise substitutions in discontinuous multiple bases of a targeted gene using base editors and the prime editing system based on CRISPR/Cas9 has been quite difficult. Here, using GT and our SSA-mediated marker excision system, we succeeded in the precise base substitution not only of single bases but also of artificial discontinuous multiple bases in the miR172 target site of the OsCly1 gene. Precise base substitution of miRNA target sites in target genes using this precise genome editing system will be a powerful tool in the production of valuable crops with improved traits.